PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA SORT CARD TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS II SDI SIKUMANA 3 KUPANG - Mersi Bani; Kristina E. Noya Nahak; Heryon Bernard Mbuik (STKIP Subang, 2026)
Bani, Mersi. 2025. The Effect of Contextual Teaching and Learning (CTL) Learning Model Assisted by Sort Card Media on Students' Learning Interest in Civics Education Subject in Grade II SDI Sikumana 3 Kupang. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University Kupang. Supervisor : 1. Kristina E. Noya Nahak, S.Pd., M.Pd : Supervisor 2. Heryon B. Mbuik, S.PAK., M.Pd. This research aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model assisted by Sort Card media on students' learning interest in Civics Education subject in grade II at SDI Sikumana 3 Kupang. The background of this research is the low learning interest of students in Civics Education learning caused by the use of conventional teaching methods that are less attractive and the lack of variety in interactive learning media. This research employs a quantitative method with a Quasi Experimental Design using Nonequivalent Control Group Design. The research population consisted of all second-grade students at SDI Sikumana 3 Kupang, totaling 50 students, with a research sample of 50 students consisting of class II C as the experimental class (25 students) and class II D as the control class (25 students). The sampling technique used was saturated sampling. The data collection instrument used a learning interest questionnaire that had been tested for validity and reliability. Data analysis techniques included normality test, homogeneity test, and hypothesis testing using Independent Sample t-test. The research results show that: there is a significant difference between the learning interest of students who use the CTL learning model assisted by Sort Card media and students who use conventional learning, the average learning interest score of experimental class students is higher than the control class, and based on the Independent Sample t-test, a significance value of 0.000 < 0.05 was obtained, which means there is a significant effect of the CTL learning model assisted by Sort Card media on students' learning interest in Civics Education subject in grade II at SDI Sikumana 3 Kupang. Therefore, the CTL learning model assisted by Sort Card media is effective in increasing students' learning interest because it is able to create contextual, interesting, interactive, and enjoyable learning.